Predispersal home range shift of an ocelot Leopardus pardalis (Carnivora: Felidae) on Barro Colorado Island, Panama - Rafael Mares; Ricardo S Moreno; Roland W. Kays; Martin Wikelski (Revista de Biología Tropical, 2008)
Home range shifts prior to natal dispersal have been rarely documented, yet the events that lead a subadult to abandon a portion of its home range and venture into unfamiliar territories, before eventually setting off to look for a site to reproduce, are probably related to the causes of dispersal itself. Here, we used a combination of manual radio-tracking and an Automated Radio Telemetry System to continuously study the movements of a subadult male ocelot (Leopardus pardalis), a solitary carnivore with sex-biased dispersal, on Barro Colorado Island, Panama, for 18 months from May 2003 through October 2004. The subadult ocelot’s parents were also radio-tracked to record possible parent-offspring interactions within their home ranges. At the age of ca. 21 months the subadult gradually began to shift its natal home range, establishing a new one used until the end of the study, in an area that had previously been used by another dispersing subadult male. Only three parent-offspring interactions were recorded during the four months around the time the range-shift occurred. The apparent peaceful nature of these encounters, along with the slow transition out of a portion of his natal home range, suggest the subadult was not evicted from his natal area by his parents. The timing of the shift, along with the subadult’s increase in weight into the weight range of adult ocelots four months after establishing the new territory, suggests that predispersal home range shifts could act as a low risk and opportunistic strategy for reaching adult size, while minimizing competition with parents and siblings, in preparation for an eventual dispersal into a new breeding territory. Rev. Biol. Trop. 56 (2): 779-787. Epub 2008 June 30. Los desplazamientos del ámbito hogareño de mamíferos subadultos previos a la dispersión natal rara vez han sido documentados. Sin embargo, los eventos que llevan a un animal subadulto a abandonar una parte de su ámbito natal, antes de buscar un sitio definitivo donde reproducirse, pueden estar relacionados con las causas de la dispersión en si. En este estudio, utilizamos una combinación de radio-telemetría manual y un Sistema de Radio-Telemetría Automatizado para estudiar de manera continua los movimientos de un ocelote (Leopardus pardalis) macho subadulto, un carnívoro solitario con dispersión sesgada sexualmente, en la Isla de Barro Colorado, Panamá, durante 18 meses (mayo 2003 hasta octubre 2004). Los padres del ocelote subadulto también fueron monitoreados por radio-telemetría para registrar posibles interacciones entre padres e hijo en sus ámbitos hogareños. A la edad aproximada de 21 meses, el ocelote subadulto comenzó a desplazar gradualmente su ámbito hogareño natal, estableciendo uno nuevo que fue ocupado hasta el final del estudio, en un área que había sido ocupada previamente por otro macho subadulto en dispersión. Se registraron solamente tres interacciones entre padres e hijo en los cuatro meses del desplazamiento. La aparente naturaleza pacífica de estos encuentros, junto con el lento abandono de una parte de su ámbito hogareño natal, sugieren que el subadulto no fue expulsado de su área natal por sus padres. El momento del desplazamiento, junto con el incremento en peso del subadulto (al peso propio de un adulto) cuatro meses después de haber establecido su nuevo territorio, sugiere que los desplazamientos del ámbito hogareño previos a la dispersión natal podrían actuar como una estrategia oportunista y de bajo riesgo para alcanzar el tamaño adulto, minimizando la competencia con padres y hermanos, en preparación para una dispersión final a un nuevo territorio para reproducirse.